Paisaje industrial postfordista y rasgos de desempleo tecnológico en la industria del Valle del Cauca - Mejía Sanabria, Carlos Alberto (Sociedad y Economía, 2005)
This paper supports the view that the industrial landscape of Valle del Cauca has been radicaily changed as part of a process of intense entrepreneurial reorganization and technological change. This process has occurred during the last decades of the XX-th century and it has had important consequences upon the management and eradication of industrial employment at the local and regional levéis. It seems that commercial and industrial firms are not requiring workers for plant expansions and, on the contrary, they go through a different way by eliminating labor positions and improving productivity Índices. This paper follows the track of the perceived changes by examining clues, features, statistics and speeches of active managers